2022
DOI: 10.1017/jmo.2022.34
|View full text |Cite
|
Sign up to set email alerts
|

Alliance management and innovation under uncertainty

Abstract: Drawing on the configuration argument of strategic fit – i.e., an effective alignment of a firm's strategy with its environment, internal structures, and processes – and the resource-based view, this paper clarifies the impact of alliance strategy, alliance management resources, and alliance management capabilities on innovation performance in collaborative ventures. This study of 441 collaborative ventures in the electronics industry offers empirical support for the configuration argument. First, greater alli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…There are opportunities for further integration of these literatures. For example, research could examine how the ecosystem leadership capabilities we have described in this paper may be embedded in firms' alliance management capabilities (Bouncken, Fredrich, & Gudergan, 2022;Schreiner, Kale, & Corsten, 2009). In addition, while we have focused on the role of agreements, standards and capabilities, structural characteristics of the networks (such as the centrality of a potential ecosystem leader in an existing network) may also affect the process of ecosystem emergence and network formation (Podolny, 2001).…”
Section: Limitations and Future Research On Ecosystem Leadershipmentioning
confidence: 99%
“…There are opportunities for further integration of these literatures. For example, research could examine how the ecosystem leadership capabilities we have described in this paper may be embedded in firms' alliance management capabilities (Bouncken, Fredrich, & Gudergan, 2022;Schreiner, Kale, & Corsten, 2009). In addition, while we have focused on the role of agreements, standards and capabilities, structural characteristics of the networks (such as the centrality of a potential ecosystem leader in an existing network) may also affect the process of ecosystem emergence and network formation (Podolny, 2001).…”
Section: Limitations and Future Research On Ecosystem Leadershipmentioning
confidence: 99%
“…However, as scholars delve deeper into research, they have concluded that the uncertainty associated with technological innovation does not always produce bad results but can be turned into a key to unlocking opportunity with effective action (Subramaniam & Loganathan, 2022); there is no contradiction between high risk caused by uncertainty and business success (Sadeh & Dvir, 2020). Through effectively assessing the risks associated with uncertainty in technological innovation, rationally prioritizing technological innovation projects (Chen, 2018), and active using partner networks and context-specific strategies at different stages (Hyvärinen et al, 2020), the uncertainty associated with innovation is effectively managed and can instead significantly enhance innovation performance (Bouncken et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, collaboration has emerged as a critical driver for technological innovations, which in turn have significant consequences for sustainability across different businesses (Bui et al, 2022). The technological innovations also present challenges and opportunities for alliance management and innovation under uncertainty (Bouncken & Gudergan, 2022. ), and in turn, the innovation challenges that are presented by the need to ensure the efficacy of such non-financial measures.…”
Section: Introductionmentioning
confidence: 99%